Investigating the crosstalk between ABCC4 and ABCC5 in 3T3-L1 adipocyte differentiation - Laddha, Ankit P.; Wahane, Aniket; Bahal, Raman; Manautou, José E. (Frontiers in Molecular Biosciences, 2024)
IntroductionThe plasma membrane-bound protein, multi-drug resistance-associated protein 4 (MRP4/ABCC4), has gained attention for its pivotal role in facilitating the efflux of a wide range of endogenous and xenobiotic molecules. Its significance in adipogenesis and fatty acid metabolism has been brought to light by recent studies. Notably, research on ABCC4 knockout (ABCC4−/−) mice has established a link between the absence of ABCC4 and the development of obesity and diabetes. Nevertheless, the specific contribution of ABCC4 within adipose tissue remains largely unexplored.MethodsTo address this gap, we conducted a study to elucidate the role of the ABCC4 transporter in mature adipocytes, using siRNA constructs to silence its gene function.ResultsThe successful knockdown of ABCC4 significantly altered lipid status and adipogenic gene expression in mature 3T3-L1 adipocytes. Intriguingly, this knockdown also altered the gene expression patterns of other ABCC transporter family members in 3T3-L1 cells. The downregulation of ABCC5 expression was particularly noteworthy, suggesting potential crosstalk between ABCC transporters in mature adipocytes. Additionally, knocking down ABCC5 resulted in significantly higher adipogenic and lipogenic gene expression levels. Oil Red O staining confirmed increased lipid accumulation following the knockdown of ABCC4 and ABCC5. Surprisingly, the simultaneous knockdown of both transporters did not show a cumulative effect on adipogenesis, rather it led to higher levels of intracellular cAMP and extracellular prostaglandin metabolite, both of which are essential signaling molecules in adipogenesis.ConclusionThese results highlight the complex interplay between ABCC4 and ABCC5 transporters in adipocyte function and suggest their individual contributions toward obesity and related disorders.